Subjects with Discordant Airways Obstruction: Lost between Spirometric Definitions of COPD - Bernd Lamprecht; Lea Schirnhofer; Bernhard Kaiser; Sonia A. Buist; David M. Mannino; Michael Studnicka (Pulmonary Medicine)
Background. Since the FEV1/FVC ratio declines with age, using the fixed ratio of 0.70 leads to overdiagnosis of COPD in older populations and underdiagnosis among young adults. Objective. To evaluate whether discordant obstructive cases (FEV1/FVC < 0.70 but ≥LLN) are a healthy population or have clinical features that would place them at increased risk. Methods. We used post-bronchodilator spirometry data from the population-based Austrian Burden of Obstructive Lung Disease (BOLD) study. Those with post-bronchodilator FEV1/FVC ratio <LLN and <0.70 were defined as concordant obstructive cases. Participants with post-bronchodilator FEV1/FVC ratio ≥LLN but <0.70 were defined as discordant obstructive cases. Results. Discordant obstructive cases were more likely to be older, male and never-smokers. Additionally they had less respiratory symptoms and less severe impairment of FEV1. However, discordant obstructive cases reported significantly more often a diagnosis of heart disease than subjects with normal lung function (27.2% vs 7.3%, P=.015). Conclusion. The clinical profile of discordant obstructive cases includes potentially important comorbid disease.